Mencintai Karena Allah: Konsep dan Aplikasinya dalam Kehidupan Sosial Berdasarkan Al-Qur'an dan Hadits serta Implikasinya di Kampus Universitas Islam Zainul Hasan Genggong Probolinggo - Afifah Agustini; Ainur Rofiq Sofa (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This study aims to analyze the concept of "loving for the sake of Allah" based on the Qur'an and Hadith and examine its application in social life, particularly within the campus environment of Zainul Hasan Islamic University, Genggong Probolinggo. The concept of loving for the sake of Allah is a spiritual value that underpins interpersonal relationships in Islam, emphasizing compassion, brotherhood, and selfless sincerity. Using a qualitative approach with field studies and documentation methods, the research involves students, lecturers, and campus administrators as subjects. The findings reveal that the values of loving for the sake of Allah are applied in various social activities on campus, such as religious programs, organizational collaboration, and community service. Qur'anic verses like Surah Ali Imran (3:31) and Hadiths on Islamic brotherhood serve as the primary references for understanding this concept. The implications show that implementing the value of loving for the sake of Allah fosters a harmonious campus atmosphere, strengthens Islamic brotherhood, and motivates students to contribute positively to the community. However, challenges in consistently applying this value arise, particularly due to external influences and a lack of deeper understanding. Therefore, strengthening religious programs and Islamic character development on campus is essential to ensure the sustainability of these values in social life.